2018
DOI: 10.3390/rs10040588
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Monitoring of the Impacts of Disaster on Human Activity Using DMSP/OLS Nighttime Light Data: A Case Study of the 2008 Wenchuan, China Earthquake

Abstract: Time series monitoring of earthquake-stricken areas is significant in evaluating post-disaster reconstruction and recovery. The time series of nighttime light (NTL) data collected by the defense meteorological satellite program-operational linescan system (DMSP/OLS) sensors provides a unique and valuable resource to study changes in human activity (HA) because of the long period of available data. In this paper, the DMSP/OLS NTL images' digital number (DN) is used as a proxy for the intensity of HA since there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Cold spots were mainly concentrated in Guangxi, Hunan, Hubei and Sichuan. The 2008 Wenchuan earthquake in Sichuan Province caused serious damage to the city's infrastructure and light source providers in the affected area, which may explain the reduction in light pollution [55]. Due to superior natural conditions, there are several nature reserves in these regions.…”
Section: The Trends and Patterns Of Light Pollution In Pas From 1992 mentioning
confidence: 99%
“…Cold spots were mainly concentrated in Guangxi, Hunan, Hubei and Sichuan. The 2008 Wenchuan earthquake in Sichuan Province caused serious damage to the city's infrastructure and light source providers in the affected area, which may explain the reduction in light pollution [55]. Due to superior natural conditions, there are several nature reserves in these regions.…”
Section: The Trends and Patterns Of Light Pollution In Pas From 1992 mentioning
confidence: 99%
“…Nighttime images include not only urban lights but also lights from fishing vessels, natural gas combustion, forest fires, etc. [ 10 ]. These images are widely utilized in research areas, such as economy assessment, regional development research, major event evaluation, and fishery monitoring [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nighttime light (NTL) has been a hot topic in remote sensing research. Because of the unique ability of NTL to reveal human activities as well as NTL’s advantages of spatiotemporal continuity and independence [1,2], NTL is widely used to estimate gross domestic product (GDP) [3,4,5], population [6,7] and electricity consumption [8,9], urbanization monitoring [10,11,12,13,14], ecological environmental changes [15], and major event assessment [16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It represents a low level of human settlement, such as towns and villages, or some irregular human activities, which may be caused by traffic or the construction of a building or a road. For example, scholars have found that low-intensity NTL can be used to explain the consistent between the maintenance of the main roads after the 2008 Wen Chuan earthquake and NTL strips on the time series NTL images from DMSP [18]. In this paper, these low-intensity NTL emitted by small size of human settlements and unstable human activities are defined as “Feeble NTL”.…”
Section: Introductionmentioning
confidence: 99%